Big Data Solution for Quality Monitoring and Improvement on Flat Steel Production*. Issue 20 (2016) - Brandenburger, Jens; Colla, Valentina; Nastasi, Gianluca; Ferro, Floriano; Schirm, Christoph; Melcher, Josef
Abstract: A new big-data handling paradigm for quality monitoring and improvement in the flat steel production is presented based on the efficient exploitation of high resolution (HR) measuring data. Based on a multi-scale data representation over multiple production stages this new concept provides simple and fast HR data access. Realized as a three-tier software architecture including a web-service for a standardized data access the potential of this new concept could be remarkably proven within two industrial pilot applications. This includes an application for data visualisation that enables the in-coil aggregation of millions of quality and process measures within seconds and an application for advanced cause-and-effect analysis based on HR data.